Pengaruh Komunikasi Perusahaan dan Komunikasi Penggunaan Terhadap Niat Beli pada Apple - Nito Fathur Rahaman (Syntax Idea)
The purpose of this research is to study company-generated social media communications, user-generated social media communications, brand passion and purchase intentions. The design in this research uses hypothesis testing or hypothesis testing, which will explain certain characteristics and relationships, to test differences between groups, or the independence of two or more variables. Hypothesis testing is performed to explain variance in dependent variables or to predict organizational outcomes. The research was conducted using a cross sectional study method where data was collected once by answering research questions collected through a questionnaire. The unit of analysis used is the individual. There are 4 variables in this research, namely social media communication created by the company, social media communication created by users, brand passion, and purchase intention. Descriptive analysis shows respondents' answers from the collected questionnaires. This research uses SPSS Statistics 22 for analysis, and the results are shown in a table that displays the mean value and standard deviation of each statement in the construct. The research results show that social media communications created by companies have a statistically significant impact on the generation of social media communications created by users. There is a statistically significant impact of company-created social media communications on brand passion. There is a statistically significant impact of social media communication carried out by users on brand passion and brand passion has a statistically significant effect on purchase intention.